Role of glial 14-3-3 gamma protein in autoimmune demyelination - Lee, De-Hyung; Steinacker, Petra; Seubert, Silvia; Turnescu-Uzat, Tanja; Melms, Arthur; Manzel, Arndt; Otto, Markus; Linker, Ralf (Journal of Neuroinflammation, 2015)
The family of 14-3-3 proteins plays an important role in the regulation of cell survival and death. Here, we investigate the role of the 14-3-3 gamma (14-3-3 ?) subunit for glial responses in autoimmune demyelination.Expression of 14-3-3 ? in glial cell culture was investigated by reverse transcription polymerase chain reaction (RT-PCR) and immunocytochemistry. 14-3-3 ? knockout mice were subjected to murine myelin oligodendrocyte-induced experimental autoimmune encephalomyelitis (MOG-EAE), an animal model mimicking inflammatory features and neurodegenerative aspects of multiple sclerosis (MS).Expression studies in cell culture confined expression of 14-3-3 ? to both, oligodendrocytes (OL) and astrocytes. RT-PCR analysis revealed an increased expression of 14-3-3 ? mRNA in the spinal cord during the late chronic phase of MOG-EAE. At that stage, EAE was more severe in 14-3-3 ? knockout mice as compared to age- and gender-matched controls. Histopathological analyses on day 56 post immunization (p.i.) revealed significantly enhanced myelin damage as well as OL injury and secondary, an increase in axonal injury and gliosis in 14-3-3 ? -/- mice. At the same time, deficiency in 14-3-3 ? protein did not influence the immune response. Further histological studies revealed an increased susceptibility towards apoptosis in 14-3-3 ?-deficient OL in the inflamed spinal cord.These data argue for a pivotal role of 14-3-3 ?-mediated signalling pathways for OL protection in neuroinflammation.
EVALuna2:22340